Inhibition test of mangosteen peel extract (Garcinia mangostana L.) against bacterial diseases of tiger grouper (Epinephellus fuscoguttatus). Issue 1 (November 2021) - Akmal, Y; Humairani, R; Muliari, M; Irfannur, I; Rinaldi, R; Harahap, M R; Zulfahmi, I
Abstract: Cultivation of tiger grouper ( Epinephelus fuscoguttatus ) in Floating Net Cages in several locations in Bireuen Regency has developed. The potential disease issue can be caused by bacteria, viruses, fungi, or parasites. The purpose of this study was to determine the effectiveness of mangosteen peel extract capsules ( Garcinia mangostana L) against bacterial disease in tiger grouper. This research was carried out in April 2019 at the MIPA Laboratory of Al Muslim University and the laboratory of PT. Centra Proteina Prima, Bireuen Regency. The design used was a completely randomized design with four treatments (0%, 10%, 20%, and 30% mangosteen peel extract capsules) with three replications. The parameters studied in this study including the diameter of the inhibition and the observation of MBC (Minimum Bacterial Concentration). The result showed that the administration of mangosteen peel extract capsules with doses of 10%, 20%, and 30% has no significant effect on reducing disease-causing bacteria in grouper grown on TSA media. Positive results were obtained on positive (+) MBC observations, presumably due to the small dose of mangosteen peel extract capsules given so that it could not kill bacteria grown in dishes with an inhibition range of 0 mm.Introduction